HUBUNGAN STIGMA DENGAN SIKAP MASYARAKAT TERHADAP PENDERITA GANGGUAN JIWA - Tia Suryaningsih; Veny Elita; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Mental disorders is syndrome of behavior patterns that are clinically meaningful and directly related to distress orsuffering and can cause disabilities in one or more of human life functions. This study aims to determine therelationship between stigma and people’s attitudes towards mental disorders in West Sidomulyo Village. This studyuses descriptive correlation design and cross sectional approach. The sample in this study were 38 respondents chosenbased on inclusion criteria using purposive sampling technique. The measuring instrument used is a questionnaire thathas been tested for validity and reliability. The data analysis used is fisher exact test. The results showed thatp value =0,009 (p < 0,05), which means that there is a significant correlation between stigma and people’s attitudes towardsindividuals with mental disorders. There is a significant relationship between stigma and people's attitudes towardspeople with mental disorders. The lower the stigma of society towards people with mental disorders, the more positivethe attitude of society towards people with mental disorders, on the other hand, if the stigma of society is high, theattitude given by society to people with mental disorders will also be negative.Based on the results of this study, it ishoped that nursing staff, especially community mental nurses, can understand the condition of people with mentaldisorders and contribute to society regarding the stigma of mental disorders by providing health education andappropriate information for the community regarding people with mental disorders.Keywords: Attitude; Mental disorders; stigma.